Effect of the beta-gamma phosphate bond of ATP on synthesis of leader RNA and mRNAs of vesicular stomatitis virus. - Green, T L (J Virol, 1984)
RNA products synthesized in vitro by vesicular stomatitis virus with normal nucleotides or imido analogs were compared by polyacrylamide gel electrophoresis. When imido ATP, which has a nonhydrolyzable beta-gamma bond, was substituted for ATP, leader RNA and DI particle product were synthesized, but appreciable mRNA synthesis was not detected. IMAGES: